2016
DOI: 10.1002/acp.3286
|View full text |Cite
|
Sign up to set email alerts
|

How do Lawyers Examine and Cross‐Examine Children in Scotland?

Abstract: In the first study to systematically assess lawyers' questioning of children in Scotland, we examined 56 trial transcripts of 5-to 17-year-old children testifying as alleged victims of sexual abuse, focusing on differences between prosecutors and defense lawyers with respect to the types of questions asked and effects on witnesses' responses. Prosecutors used more invitations, directives, and option-posing prompts than defense lawyers, who used more suggestive prompts than prosecutors. Children were more unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 45 publications
6
60
1
Order By: Relevance
“…As in other studies focused on in‐court questioning (e.g., Andrews & Lamb, ; Andrews et al, ; Klemfuss et al, ; Stolzenberg & Lyon, ), and as we anticipated, option‐posing questions were used most frequently by all DMF participants. Such questions thus seem to characterize the approach adopted by legal professionals questioning witnesses.…”
Section: Discussionsupporting
confidence: 54%
“…As in other studies focused on in‐court questioning (e.g., Andrews & Lamb, ; Andrews et al, ; Klemfuss et al, ; Stolzenberg & Lyon, ), and as we anticipated, option‐posing questions were used most frequently by all DMF participants. Such questions thus seem to characterize the approach adopted by legal professionals questioning witnesses.…”
Section: Discussionsupporting
confidence: 54%
“…Problematically, children often attempt to answer complex closed‐ended questions even if they are incomprehensible or unanswerable (Waterman, Blades, & Spencer, ) likely because a simple “yes” or “no” often satisfies the questioner (Walker, ). Field research consistently demonstrates that both prosecutors and defense lawyers mostly ask option‐posing “yes/no” questions (Hanna et al, ; Klemfuss, Quas, & Lyon, ; Zajac & Cannan, ) and that defense lawyers ask more suggestive questions than prosecutors do (Andrews & Lamb, ; Klemfuss et al, ; Stolzenberg & Lyon, ; Zajac & Cannan, ). Not only do closed‐ended and suggestive questions elicit erroneous responses and self‐contradictions (Lamb, Orbach, Hershkowitz, Horowitz, et al, ; Zajac et al, ; Zajac & Hayne, ) but they also tend to be more linguistically complex (Andrews & Lamb, ; Walker et al, ).…”
Section: Question Complexity In Courtroomsmentioning
confidence: 99%
“…Not only do closed‐ended and suggestive questions elicit erroneous responses and self‐contradictions (Lamb, Orbach, Hershkowitz, Horowitz, et al, ; Zajac et al, ; Zajac & Hayne, ) but they also tend to be more linguistically complex (Andrews & Lamb, ; Walker et al, ). Research has also determined that suggestive questions vary, with some being more complex than others (e.g., tagged prompts; Andrews & Lamb, ; Evans, Stolzenberg, & Lyon, ; Walker, ). For example, Andrews and Lamb () reported that tagged suggestive questions (e.g., “And then you lied to your mom, isn't that right?”) were more complex than untagged suggestive questions (e.g., “Why did you lie to your mom?” when the child had not admitted lying).…”
Section: Question Complexity In Courtroomsmentioning
confidence: 99%
See 2 more Smart Citations